Molten salt aluminum-sulfur battery and preparation method of high-load positive electrode

The preparation of sulfur positive electrodes through room temperature self-diffusion and dry powder rolling technology solves the problems of volatility and low loading of active substances in the preparation of sulfur positive electrodes, and realizes electrodes with high loading and structural strength, which are suitable for high energy density battery applications.

CN119133353APending Publication Date: 2024-12-13XI AN JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411221937.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art has problems in the preparation of sulfur positive electrodes, the production process is complicated and the energy consumption is high, and the electrode active material load is low, making it difficult to meet the requirements of industrial battery energy density.

Method used

The sulfur positive electrode preparation method with room temperature self-diffusion is adopted. Through grinding and dry powder rolling technology, the thermal diffusion process is avoided, and electrode preparation with high active substance load and structural strength is achieved.

Benefits of technology

This method simplifies the preparation process, reduces energy consumption, improves electrode consistency and load, meets the needs of high energy density, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133353A_ABST
    Figure CN119133353A_ABST
Patent Text Reader

Abstract

The invention discloses a molten salt aluminum-sulfur battery and a preparation method of a high-load positive electrode, and belongs to the technical field of electrochemical energy storage, the method comprises the following steps: step 1, weighing an active substance and a conductive agent according to a certain proportion, fully grinding by using an agate grinding machine, and uniformly mixing to obtain a mixture; 2, adding a binder into the mixture, and grinding until the mixture is gathered together to form a flaky material with certain toughness; 3, dry powder rolling is conducted on the flaky material, an electric double-roller machine is adjusted, the distance between rollers is gradually reduced, rolling is conducted repeatedly, and then the material with the needed thickness is obtained; and 4, placing and drying the rolled material, and cutting into pieces to obtain the electrode. According to the invention, the preparation process of the sulfur positive electrode material is simplified, the room-temperature sulfur self-diffusion is adopted to replace molten sulfur thermal diffusion, the rolling method is used for preparing the pole piece with high-activity substance loading capacity, the operation is simple and easy to control, and the preparation method has important significance for improving the energy density of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and specifically relates to a positive electrode suitable for a molten salt aluminum-sulfur battery, which is prepared by self-diffusion at room temperature and has high active material loading, high strength and good consistency, and a method for preparing a molten salt aluminum-sulfur battery. Background Art

[0002] The vigorous development of energy storage technology is of great significance to the stable operation of the power grid system. Among them, electrochemical energy storage has attracted widespread attention due to its advantages of environmental protection, energy saving and good environmental adaptability. Molten salt aluminum-sulfur battery is an electrochemical energy storage technology with low cost, high safety and high power characteristics. Among them, the sulfur positive electrode is an important component of the electrochemical energy storage system. In order to improve the insulation of the positive electrode sulfur, the currently widely used strategy is to use carbon materials as a conductive host and sulfur composite. Most researchers use methods such as melt diffusion, steam impregnation, thermal diffusion and chemical precipitation to prepare sulfur-carbon composite materials, among which thermal diffusion method is the most widely used. The thermal diffusion method is to heat treat the mixture of active material sulfur and conductive host carbon under medium temperature conditions for about 10-12h, where the heat treatment temperature is about 155-160℃, which is greater than the melting point of sulfur (115℃). When the temperature rises, the molten sulfur is encapsulated into the pore structure of the carbon material due to capillary force. After the temperature is reduced, the sulfur solidifies to obtain a sulfur-carbon composite material. However, during the heat treatment process, some active substances will volatilize as the temperature rises, resulting in mass loss. Further testing is needed to determine the remaining sulfur content in the composite material. The preparation process is complicated and consumes a lot of energy and time.

[0003] Secondly, the current method used by researchers to prepare battery electrodes mostly uses slurry coating. This method adds an organic solvent to mix active materials with conductive agents and other materials to form a slurry, and then coats the slurry on the current collector to obtain a pole piece. Slurrying generally uses N-methylpyrrolidone (NMP) as a solvent. In order to quickly dry the coated electrode, the NMP in the electrode slurry needs to be evaporated quickly. The NMP vapor in the electrode preparation process is not only toxic to the human body but also pollutes the air. At the same time, the loading of electrode active materials prepared by the slurry coating method depends on the adhesion between the active material and the current collector. Thicker electrode material coatings can easily cause problems such as electrode powder loss and structural collapse. At the same time, the final dried electrode still needs to use a rolling process to ensure that the electrode material is in close contact with the current collector to eliminate the pores formed after the solvent evaporates. It is difficult to ensure the consistency of the electrode during actual use.

[0004] In addition, the electrode active material loading used in the current sulfur cathode research is mostly low (1-2 mg cm -2), which means that the active material content per unit area of ​​the electrode is low. Although it shows a good electrode mass specific capacity in the test battery, this low-load sulfur cathode and complex preparation process are obviously difficult to meet the requirements of the industrial field for improving the overall discharge capacity and energy density of the battery. Therefore, the development of a sulfur cathode preparation method with high loading, simple preparation process and stable electrochemical performance is of great significance for improving the energy density of the battery and promoting the industrialization of low-cost aluminum-sulfur batteries. Summary of the invention

[0005] The present invention proposes a method for preparing a room temperature self-diffusion sulfur positive electrode and a molten salt aluminum-sulfur battery, which does not require a molten sulfur thermal diffusion process. This method not only enables the electrode to have good structural strength, but also can achieve the preparation of electrodes with different active material loadings by precisely controlling the thickness of the electrode sheet.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a high-load positive electrode for a molten salt aluminum-sulfur battery comprises the following steps:

[0008] Step 1: Grind and evenly mix the active material and the conductive agent to obtain a mixture; the active material is sulfur or a sulfur-selenium mixture;

[0009] Step 2: Add the binder to the mixture and press until the mixture gathers into a mass;

[0010] Step 3: rolling the mass, gradually reducing the distance between the rollers, and rolling the mass multiple times until the mass is rolled to a desired thickness to obtain a sheet;

[0011] Step 4: Dry and cut the sheet into pieces to obtain electrodes.

[0012] Furthermore, in step 1, the mass ratio of the active material to the conductive agent is (3-8):2.

[0013] Furthermore, in step 1, the conductive agent is Ketjen black, carbon nanotubes or acetylene black.

[0014] Furthermore, in step 1, the active material and the conductive agent are ground using an agate grinder.

[0015] Furthermore, in step 2, the binder is polytetrafluoroethylene.

[0016] Furthermore, in step 3, the thickness is 60 μm-160 μm.

[0017] Furthermore, in step 3, the agglomerate is rolled using an electric double roller machine.

[0018] A method for preparing a molten salt aluminum-sulfur battery comprises the following steps:

[0019] S1. Prepare an electrode using the method according to claim 1;

[0020] S2. Use the electrode prepared in S1 as the positive electrode of the battery, the aluminum sheet as the negative electrode, and an inorganic molten salt as the electrolyte to assemble the battery.

[0021] Furthermore, in step S2, the inorganic molten salt is a quaternary inorganic molten salt or a quaternary inorganic molten salt saturated with aluminum sulfide.

[0022] Furthermore, the quaternary molten salt is a mixture of aluminum chloride (AlCl3), sodium chloride (NaCl), lithium chloride (LiCl) and potassium chloride (KCl).

[0023] Compared with the prior art, the present invention is beneficial in that:

[0024] 1) The method for preparing sulfur positive electrode of the present invention does not require thermal diffusion process, is simple to operate, saves energy, and meets the requirements of future large-scale production. When studying chalcogen elements (sulfur, selenium, etc.) as electrode active substances, researchers will mix the conductive carbon material with the active substance and then conduct medium-temperature heat treatment (150-250℃10-12h), that is, use thermal diffusion to fully disperse the active substance (sulfur, selenium, etc.) and the conductive agent. The preparation process is relatively complicated and has high energy consumption. At the same time, during the thermal diffusion process, part of the active substance will volatilize as the temperature rises, causing mass loss. The mass of the active substance in the final mixture is not equal to the original added mass. Therefore, further testing (such as thermogravimetric analysis) is required to determine the actual proportion of the active substance in the mixture. The present invention uses a grinder for grinding, making full use of the spontaneous diffusion of chalcogen elements in high specific surface area carbon materials at room temperature, avoiding medium-temperature heat treatment in the electrode preparation process, and the corresponding electrode exhibits better electrochemical properties than hot-melt sulfur electrodes. The preparation method is simpler, easy to operate, reduces energy consumption, and is safe and reliable;

[0025] 2) The sulfur positive electrode prepared by rolling the ground dry powder disclosed in the present invention has a high and easily controllable active material loading. A higher loading means that there is a larger mass of active material in the electrode per unit area or volume. When the electrode is applied to a battery, the increase in the mass of the active material can effectively increase the battery capacity and battery energy density, and can meet the needs of large-scale application and production in the future. In the present invention, the positive electrode active material loading can be regulated by controlling the proportion of the active material or the thickness of the electrode sheet. It is only necessary to adjust the mass of the active material before rolling or to control the distance between the rollers of the roller machine during rolling to obtain electrodes with different loadings. The parameters are flexible and adjustable, and the operation is simple.

[0026] 3) The electrode prepared by the dry powder rolling of the present invention can significantly improve the electrode consistency, the prepared electrode has good structural strength, and the preparation process has a lower production cost. In the process of mass electrode preparation, electrode consistency is an important factor affecting the final quality of the battery. Electrodes with poor consistency will lead to uneven quality of batteries in the same batch, affecting large-scale production. At present, most of the methods for preparing battery electrodes are pulping and coating methods. This method is to add organic solvents to mix active substances and conductive agents and other materials to make slurry and then coat to obtain pole pieces. The electrode loading depends on the adhesion between the active substance and the current collector. When the electrode material is thicker, the coating is very prone to problems such as powder loss and collapse, resulting in poor consistency of the pole pieces during actual use. Different from the traditional pulping and coating method, the positive electrode prepared by the dry powder rolling provided by the present invention, the active substance and the conductive agent are mixed in powder form during grinding, and the material is prepared by dry mixing. The mixing is more uniform and easy to store. At the same time, the thickness of the electrode can be accurately adjusted by a roller press, and the thickness of the final pole piece is uniform, the operation is simple, and the parameters are easy to control, so that electrodes with good consistency can be obtained. Secondly, the electrode preparation process is to apply pressure through rollers, gradually reduce the spacing between rollers at very small intervals, and repeatedly roll from thick to thin until an electrode with uniform thickness is obtained. This method of gradually increasing pressure on the electrode surface and repeatedly rolling makes the electrode have a suitable compaction density and good structural strength, and is not easy to fall off and collapse. It is not easy to be crushed due to electrochemical reactions when used in batteries, which improves the stability of the electrode. Finally, the cost of preparing the positive electrode in the present invention is low, the grinder and electric roller machine used in the preparation process can be used multiple times, and the binder uses low-cost polytetrafluoroethylene.

[0027] The high-load sulfur positive electrode preparation method of the present invention does not require a molten sulfur thermal diffusion step, and the parameters are easy to control, the operation is simple and the cost is low. The prepared positive electrode has the characteristics of high active material loading, good structural strength and excellent consistency. It can be applied to molten salt aluminum-sulfur batteries to improve battery capacity and energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart of the present invention;

[0029] Figure 2a The cycle performance curve of the positive electrode obtained in Example 1 of the present invention in an aluminum ion battery;

[0030] Figure 2b Voltage curve of the positive electrode obtained in Example 1 of the present invention in an aluminum ion battery;

[0031] Figure 3a The cycle performance curve of the positive electrode obtained in Example 2 of the present invention in an aluminum ion battery;

[0032] Figure 3bThe voltage curve of the positive electrode obtained in Example 2 of the present invention in an aluminum ion battery;

[0033] Figure 4a The cycle performance curve of the positive electrode obtained in Example 3 of the present invention in an aluminum ion battery;

[0034] Figure 4b The voltage curve of the positive electrode obtained in Example 3 of the present invention in an aluminum ion battery;

[0035] Figure 5a The cycle performance curve of the positive electrode obtained in Example 4 of the present invention in an aluminum ion battery;

[0036] Figure 5b The voltage curve of the positive electrode obtained in Example 4 of the present invention in an aluminum ion battery;

[0037] Figure 6a The cycle performance curve of the positive electrode obtained in Example 5 of the present invention in an aluminum ion battery;

[0038] Figure 6b The voltage curve of the positive electrode obtained in Example 5 of the present invention in an aluminum ion battery;

[0039] Figure 7a The cycle performance curve of the positive electrode obtained in Example 6 of the present invention in an aluminum ion battery;

[0040] Figure 7b The voltage curve of the positive electrode obtained in Example 6 of the present invention in an aluminum ion battery;

[0041] Figure 8a The cycle performance curve of the positive electrode obtained in Example 7 of the present invention in an aluminum ion battery;

[0042] Figure 8b The voltage curve of the positive electrode obtained in Example 7 of the present invention in an aluminum ion battery;

[0043] Figure 9a The cycle performance curve of the positive electrode obtained in comparative example 1 of the present invention in an aluminum ion battery;

[0044] Figure 9b The voltage curve of the positive electrode obtained in comparative example 1 of the present invention in an aluminum ion battery;

[0045] Fig.10a The cycle performance curve of the positive electrode obtained in comparative example 2 of the present invention in an aluminum ion battery;

[0046] Fig.10b The voltage curve of the positive electrode obtained in comparative example 2 of the present invention in an aluminum ion battery;

[0047] Fig.11 Schematic diagram of the homemade experiment. DETAILED DESCRIPTION

[0048] The present invention innovatively proposes a new method for preparing sulfur positive electrodes. This method does not require the thermal diffusion process of molten sulfur, but only requires simple grinding and rolling steps. By adjusting the proportion of active materials or controlling the distance between rollers, different thicknesses of pole pieces can be obtained, thereby obtaining electrodes with different active material loadings. This method is simple to operate and the parameters are easy to control. At the same time, the prepared electrodes have good consistency, high structural strength and high loading (>4mg cm -2 ) can be applied to batteries to improve battery capacity and energy density, which is of great significance to large-scale energy storage technology.

[0049] The method for preparing a high-load positive electrode for a molten salt aluminum-sulfur battery according to the present invention is described in detail below, comprising the following steps:

[0050] S1. Weigh the active material and the conductive agent respectively, according to the mass ratio of (3-8):2, place them in an agate grinder and grind them thoroughly to mix them evenly to obtain a mixture;

[0051] S2, adding a binder to the mixture obtained in S1, the amount of which is 25wt% of the mass of the mixture, and pressing after mixing until the mixture aggregates into a mass with a certain toughness;

[0052] S3, putting the above mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the material reaches the required thickness to obtain a sheet;

[0053] S4. Place the rolled sheet in a vacuum drying oven for about 30 minutes for drying, cut it into the required size using a slicer to obtain an electrode, weigh the electrode and calculate the electrode active material loading.

[0054] Furthermore, the active substance in step 1 is sulfur or a sulfur-selenium mixture, the conductive agent is a high specific surface area carbon material, such as Ketjen black (KB), carbon nanotubes (CNT) or acetylene black (AB), the grinding time of the agate grinder is 30 minutes, the mortar speed is 10 rpm, and the pestle speed is 40-60 rpm.

[0055] Furthermore, the binder in step 2 uses polytetrafluoroethylene.

[0056] Furthermore, steps 1-4 are performed in an air environment at room temperature, and step 5 is performed in a glove box filled with an inert gas or in a low water and oxygen environment.

[0057] A method for preparing a molten salt aluminum-sulfur battery, comprising preparing a high-load positive electrode by the above method, then taking the above-prepared electrode as the battery positive electrode, an aluminum sheet as the negative electrode, and an inorganic molten salt as the electrolyte, assembling the battery to obtain a molten salt aluminum-sulfur battery, and performing an electrochemical performance test on the molten salt aluminum-sulfur battery.

[0058] Furthermore, the electrolyte used is a quaternary inorganic molten salt or a quaternary inorganic molten salt saturated with aluminum sulfide, wherein the quaternary molten salt is a mixture of aluminum chloride (AlCl3), sodium chloride (NaCl), lithium chloride (LiCl) and potassium chloride (KCl), and the optimal operating temperature of the battery is 130°C.

[0059] The following are relevant embodiments for verifying the technology described in the present invention:

[0060] Example 1

[0061] A method for preparing a high-load electrode for a molten salt aluminum-sulfur battery is as follows:

[0062] S1. Weigh sulfur (S) and Ketjen black (KB) in a mass ratio of 3:2 respectively, place them in an agate grinder and grind them for 30 minutes at a pestle speed of 40 rpm, grind them thoroughly to make them uniformly mixed, and obtain a mixture;

[0063] S2, adding polytetrafluoroethylene as a binder to the mixture obtained in S1, the addition amount being 25wt% of the mass of the mixture, grinding and pressing until the mixture aggregates into a mass with a certain toughness;

[0064] S3, placing the above-mentioned mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the mass becomes a sheet with a thickness of 80 μm;

[0065] S4. Place the rolled sheet in a vacuum drying oven for about 30 minutes to dry, cut it with a slicer to obtain an electrode (Φ10), weigh the electrode and calculate the electrode active material loading to be 5.0 mg cm -2 .

[0066] A method for preparing a molten salt aluminum-sulfur battery, wherein a high-load positive electrode is prepared by the above method, and then the electrode prepared above is used as the positive electrode of the battery, an aluminum sheet is used as the negative electrode, and a quaternary inorganic molten salt (NaCl-KCl-LiCl-AlCl3-Al2S3) saturated with aluminum sulfide is used as the electrolyte. The assembled battery is subjected to a constant current charge and discharge test at a current density of 1C. The test results are as follows: Figure 2a and Figure 2b shown.

[0067] Example 2

[0068] A method for preparing a high-load electrode for a molten salt aluminum-sulfur battery is as follows:

[0069] S1. Weigh sulfur (S) and Ketjen black (KB) in a mass ratio of 5:2 respectively, place them in an agate grinder and grind them for 30 minutes at a pestle speed of 50 rpm, grind them thoroughly to make them uniformly mixed, and obtain a mixture;

[0070] S2, adding polytetrafluoroethylene as a binder to the mixture obtained in S1, the addition amount being 25wt% of the mass of the mixture, grinding and pressing until the mixture aggregates into a mass with a certain toughness;

[0071] S3, placing the above-mentioned mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the mass becomes a sheet with a thickness of 90 μm;

[0072] S4. The rolled sheet was placed in a vacuum drying oven for about 30 minutes for drying. The electrode (Φ10) was cut using a slicer. The electrode was weighed and the electrode active material loading was calculated to be 7.64 mg cm -2 .

[0073] A method for preparing a molten salt aluminum-sulfur battery, comprising preparing a high-load positive electrode by the above method, and then taking the above-prepared electrode as the battery positive electrode, and the aluminum sheet as the negative electrode, and using a quaternary inorganic molten salt (NaCl-KCl-LiCl-AlCl3-Al2S3) saturated with aluminum sulfide as the electrolyte, and assembling the battery to perform a constant current charge and discharge test at a current density of 1C. The test results are shown in Figure 3 (a, b).

[0074] Example 3

[0075] A method for preparing a high-load electrode for a molten salt aluminum-sulfur battery is as follows:

[0076] S1. Weigh sulfur (S) and Ketjen black (KB) in a mass ratio of 8:2 respectively, place them in an agate grinder and grind them for 30 minutes at a pestle speed of 60 rpm, grind them thoroughly to make them uniformly mixed, and obtain a mixture;

[0077] S2, adding polytetrafluoroethylene as a binder to the mixture obtained in S1, the addition amount being 25wt% of the mass of the mixture, grinding and pressing until the mixture aggregates into a mass with a certain toughness;

[0078] S3, placing the above-mentioned mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the mass becomes a sheet with a thickness of 110 μm;

[0079] S4. Place the rolled sheet in a vacuum drying oven for about 30 minutes to dry, cut it with a slicer to obtain an electrode (Φ10), weigh the electrode and calculate the electrode active material loading to be 13.7 mg cm -2 ;

[0080] S5. Take the electrode prepared as above as the positive electrode of the battery, the aluminum sheet as the negative electrode, and the quaternary inorganic molten salt (NaCl-KCl-LiCl-AlCl3-Al2S3) saturated with aluminum sulfide as the electrolyte. The assembled battery is subjected to constant current charge and discharge test at a current density of 1C. The test results are shown in Figure 4 (a, b).

[0081] Example 4

[0082] A method for preparing a high-load electrode for a molten salt aluminum-sulfur battery is as follows:

[0083] S1. Weigh sulfur (S) and Ketjen black (KB) in a mass ratio of 3:2 respectively, place them in an agate grinder and grind them for 30 minutes at a pestle speed of 40 rpm, grind them thoroughly to make them uniformly mixed, and obtain a mixture;

[0084] S2, adding polytetrafluoroethylene as a binder to the mixture obtained in S1, the addition amount being 25wt% of the mass of the mixture, grinding and pressing until the mixture aggregates into a mass with a certain toughness;

[0085] S3, placing the above-mentioned mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the mass becomes a sheet with a thickness of 160 μm;

[0086] S4. The rolled sheet was placed in a vacuum drying oven for about 30 minutes for drying. The electrode (Φ10) was cut using a slicer. The electrode was weighed and the electrode active material loading was calculated to be 9.84 mg cm -2 .

[0087] A method for preparing a molten salt aluminum-sulfur battery, wherein a high-load positive electrode is prepared by the above method, and then the electrode prepared above is used as the positive electrode of the battery, an aluminum sheet is used as the negative electrode, and a quaternary inorganic molten salt (NaCl-KCl-LiCl-AlCl3-Al2S3) saturated with aluminum sulfide is used as the electrolyte. The assembled battery is subjected to a constant current charge and discharge test at a current density of 1C. The test results are as follows: Figure 5a and Figure 5b shown.

[0088] Example 5

[0089] A method for preparing a high-load electrode for a molten salt aluminum-sulfur battery is as follows:

[0090] S1. Weigh sulfur (S) and carbon nanotubes (CNT) in a mass ratio of 3:2 respectively, place them in an agate grinder and grind them for 30 minutes at a pestle speed of 40 rpm, and grind them thoroughly to make them uniformly mixed to obtain a mixture;

[0091] S2, adding polytetrafluoroethylene as a binder to the mixture obtained in S1, the addition amount being 25wt% of the mass of the mixture, grinding and pressing until the mixture aggregates into a mass with a certain toughness;

[0092] S3, placing the above-mentioned mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the mass becomes a sheet with a thickness of 60 μm;

[0093] S4. The rolled sheet was placed in a vacuum drying oven for about 30 minutes for drying. The electrode (Φ10) was cut using a slicer. The electrode was weighed and the electrode active material loading was calculated to be 4.48 mg cm -2 .

[0094] A method for preparing a molten salt aluminum-sulfur battery, comprising preparing a high-load positive electrode by the above method, and then taking the above-prepared electrode as the battery positive electrode, an aluminum sheet as the negative electrode, and a quaternary inorganic molten salt (NaCl-KCl-LiCl-AlCl3-Al2S3) saturated with aluminum sulfide as the electrolyte. The assembled battery is subjected to a constant current charge and discharge test at a current density of 1C, and the test results are shown in Figure 6 (a, b).

[0095] Example 6

[0096] A method for preparing a high-load electrode for a molten salt aluminum-sulfur battery is as follows:

[0097] S1. Weigh sulfur (S) and acetylene black (AB) in a mass ratio of 3:2, place them in an agate grinder and grind them for 30 minutes at a pestle speed of 40 rpm to obtain a mixture;

[0098] S2, adding polytetrafluoroethylene as a binder to the mixture obtained in S1, the addition amount being 25wt% of the mass of the mixture, grinding and pressing until the mixture aggregates into a mass with a certain toughness;

[0099] S3, placing the above-mentioned mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the mass becomes a sheet with a thickness of 70 μm;

[0100] S4. The rolled sheet was placed in a vacuum drying oven for about 30 minutes for drying. The electrode (Φ10) was cut using a slicer. The electrode was weighed and the electrode active material loading was calculated to be 4.54 mg cm -2 .

[0101] A method for preparing a molten salt aluminum-sulfur battery, wherein a high-load positive electrode is prepared by the above method, and then the electrode prepared above is used as the positive electrode of the battery, an aluminum sheet is used as the negative electrode, and a quaternary inorganic molten salt (NaCl-KCl-LiCl-AlCl3-Al2S3) saturated with aluminum sulfide is used as the electrolyte. The assembled battery is subjected to a constant current charge and discharge test at a current density of 1C. The test results are as follows: Figure 7a and Figure 7b shown.

[0102] Example 7

[0103] A method for preparing a high-load electrode for a molten salt aluminum-sulfur battery is as follows:

[0104] S1. Weigh active materials sulfur (S) and selenium (Se) and conductive agent Ketjen black (KB) respectively, with a mass ratio of 3:2, wherein the molar ratio of S to Se is 7:3, place them in an agate grinder and grind them for 30 minutes at a pestle speed of 40 rpm, grind them thoroughly to make them uniformly mixed, and obtain a mixture;

[0105] S2, adding polytetrafluoroethylene as a binder to the mixture obtained in S1, the addition amount being 25wt% of the mass of the mixture, grinding and pressing until the mixture aggregates into a mass with a certain toughness;

[0106] S3, placing the above-mentioned mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the mass becomes a sheet with a thickness of 80 μm;

[0107] S4. Place the rolled sheet in a vacuum drying oven for about 30 minutes to dry, cut it with a slicer to obtain an electrode (Φ10), weigh the electrode and calculate the electrode active material loading to be 7.0 mg cm -2 .

[0108] A method for preparing a molten salt aluminum-sulfur battery, wherein a high-load positive electrode is prepared by the above method, and then the electrode prepared above is used as the positive electrode of the battery, the aluminum sheet is used as the negative electrode, and a quaternary inorganic molten salt (NaCl-KCl-LiCl-AlCl3) is used as the electrolyte. The assembled battery is subjected to a constant current charge and discharge test at a current density of 1C. The test results are as follows: Figure 8a and Figure 8b shown.

[0109] Comparative Example 1

[0110] Comparative Example 1, the difference is that a molten sulfur thermal diffusion process is added after step 1. The specific steps are as follows:

[0111] S1. Weigh sulfur (S) and Ketjen black (KB) in a mass ratio of 3:2 respectively, place them in an agate grinder and grind them for 30 minutes at a pestle speed of 40 rpm, grind them thoroughly to make them uniformly mixed, and obtain a mixture;

[0112] S2. Place the mixture in a tube furnace to place it in a vacuum environment, heat it from room temperature to 160°C at a heating rate of 2°C / min, keep it at that temperature for 10 hours, then cool it to room temperature at the same rate, and take out the mixture;

[0113] S3, adding polytetrafluoroethylene as a binder to the mixture obtained in S2, the addition amount being 25wt% of the mass of the mixture, grinding and pressing until the mixture aggregates into a mass with a certain toughness;

[0114] S4, placing the above-mentioned mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the mass becomes a sheet with a thickness of 80 μm;

[0115] S5. Place the rolled sheet in a vacuum drying oven for about 30 minutes to dry, cut it with a slicer to obtain an electrode (Φ10), weigh the electrode and calculate the electrode active material loading to be 5.1 mg cm -2 ;

[0116] S6. Take the electrode prepared above as the positive electrode of the battery, the aluminum sheet as the negative electrode, and use the quaternary inorganic molten salt (NaCl-KCl-LiCl-AlCl3-Al2S3) saturated with aluminum sulfide as the electrolyte. The assembled battery is subjected to constant current charge and discharge test at a current density of 1C. The test results are as follows: Figure 9a and Figure 9b shown.

[0117] Comparative Example 2

[0118] Comparative Example 7 is different in that a heat treatment operation of the sulfur and selenium mixture is added after step 1. The specific steps are as follows:

[0119] S1. Weigh active materials sulfur (S) and selenium (Se) and conductive agent Ketjen black (KB) respectively, with a mass ratio of 3:2, wherein the molar ratio of S to Se is 7:3, place them in an agate grinder and grind them for 30 minutes at a pestle speed of 40 rpm, grind them thoroughly to make them uniformly mixed, and obtain a mixture;

[0120] S2, placing the mixture in a tube furnace to place it in a vacuum environment, heating it from room temperature to 200°C at a heating rate of 2°C / min, keeping it at that temperature for 12 hours, then cooling it to room temperature at the same rate, and taking out the mixture;

[0121] S2, adding polytetrafluoroethylene as a binder to the mixture obtained in S2, the addition amount being 25wt% of the mass of the mixture, grinding and pressing until the mixture aggregates into a mass with a certain toughness;

[0122] S3, placing the above-mentioned mass into an electric roller machine for rolling, adjusting the roller machine, gradually reducing the roller spacing and repeatedly rolling until the mass becomes a sheet with a thickness of 100 μm;

[0123] S4. The rolled sheet was placed in a vacuum drying oven for about 30 minutes for drying. The electrode (Φ10) was cut using a slicer. The electrode was weighed and the electrode active material loading was calculated to be 6.4 mg cm -2 ;

[0124] S5. Take the electrode prepared above as the positive electrode of the battery, the aluminum sheet as the negative electrode, and the quaternary inorganic molten salt (NaCl-KCl-LiCl-AlCl3) as the electrolyte. The assembled battery is subjected to constant current charge and discharge test at a current density of 1C. The test results are as follows: Fig.10a and Fig.10b shown.

[0125] According to the high-load positive electrode material for medium-temperature molten salt aluminum-sulfur batteries prepared in the above embodiment, the positive electrode active material is sulfur or a sulfur-selenium mixture, the conductive agent is a carbon material, there is no need for thermal diffusion of molten sulfur, and the sulfur is self-diffused at room temperature only by grinding. The positive electrode prepared after dry powder rolling has a conductivity greater than 4 mg cm -2 The battery has a higher active material loading, uses aluminum sheet as the negative electrode, and inorganic molten salt as the electrolyte to assemble the battery. The optimal operating temperature of the battery is 130°C, the voltage window is 0.6-1.4V, and the battery is subjected to constant current charge and discharge tests at a current density of 1C.

[0126] In the present invention, Examples 1-7 respectively verify the heat-free diffusion process, where the active material sulfur or selenium diffuses by itself at room temperature, and by changing the type of conductive agent or adjusting the proportion of active material and the thickness of the electrode, a high loading (4.48-13.7 mg cm -2 ) positive electrode and applied to a molten salt aluminum-sulfur battery to test the electrochemical performance of the battery; Comparative Examples 1-2 provide the electrochemical performance of the positive electrode prepared by heat treating sulfur or a sulfur-selenium mixture and a conductive agent, i.e. increasing the thermal diffusion process, in an aluminum-sulfur battery.

[0127] first, Figure 2a , Figure 2b , Figure 3a , Figure 3b , Figure 4a , Figure 4b , Figure 5a and Figure 5b Corresponding to Examples 1-4, sulfur (S) and Ketjen black (KB) are used as active materials and conductive agents in the electrodes, and there is no molten sulfur thermal diffusion step. The electrode loading is changed by adjusting the active material ratio and the electrode thickness. After assembling the battery, the cycle performance diagram and the charge and discharge curve are obtained. Figure 2a It can be seen that the battery in Example 1 exhibits excellent cycle stability, with a first cycle discharge capacity of 341 mAh g -1 , can stably cycle 1000 times, and the battery polarization voltage is as low as about 220mV ( Figure 2b ), the battery exhibits excellent cycle stability and reversibility. Comparison of the battery cycle performance diagram after adding the molten sulfur thermal diffusion step in Example 1 ( Figure 9a ), the battery's first discharge capacity reaches 350mAh g -1 However, the battery capacity rapidly decays to 300 mAh g after 10 cycles. -1 , can only stably cycle 100 times, the cycle life is one tenth of that of Example 1, and the voltage platform during the charge and discharge process ( Figure 9b ) is basically the same as the platform position in Example 1, and the battery polarization voltage is equivalent, indicating that the redox reaction mechanism of the two batteries is the same. This proves that thermal diffusion of molten sulfur is not a necessary step in the preparation of the electrode. The pole piece obtained by grinding at room temperature only shows a longer cycle life and a higher discharge capacity after being assembled into a battery, which confirms the feasibility of not heat-treating sulfur or sulfur-selenium mixture in step 1 of the present invention. The preparation process is simpler and more efficient, reduces energy consumption, and has no mass loss of active substances. In Example 2 and Example 3, the ratio of sulfur (S) to Ketjen black (KB) is 5:2 and 8:2, respectively, and 7.64 mg cm -2 With 13.7 mg cm -2 The ultra-high active material loading of the corresponding battery can be cycled for more than 1000 times, with a relatively excellent cycle life. The battery of Example 2 shows about 240 mAh g -1 The first cycle specific capacity ( Figure 3a ), but the discharge capacity fluctuates within a small range; after increasing the proportion of active material again in Example 3, the first cycle specific capacity of the battery is greatly reduced to 45 mAh g -1 ( Figure 4a ), the coulombic efficiency fluctuates frequently between 96% and 99%, the battery cycle stability and reversibility are poor, and the utilization rate of the positive electrode active material is extremely low. At the same time, compared with Example 1, the battery polarization voltage of Examples 2 and 3 increases to about 450-500mV ( Figure 3b and Figure 4b), which shows that directly increasing the proportion of active materials does not have a beneficial effect on the battery discharge capacity, and will significantly reduce the cycle stability and battery reversibility, which may be due to the poor conductivity of sulfur as an active material. Example 4 Adjusting the thickness of the pole piece to 160 μm to obtain 9.84 mg cm -2 The high loading capacity of Figure 5a , the battery discharge capacity reaches 250mAh g -1 , but the capacity and coulomb efficiency fluctuate significantly, and the battery discharge curve jitters at low potential ( Figure 5b ), the battery stability is poor. As can be seen from Examples 1-4, in the process of preparing high-load electrodes of the present invention, the electrode load is regulated within a certain range by changing the proportion of active materials or the thickness of the electrode sheet. While obtaining a high load, a part of the cycle stability or discharge capacity may be sacrificed. Therefore, it is particularly important to find a balance between electrode load and battery performance.

[0128] Figure 5a , Figure 5b , Figure 6a and Figure 6b Corresponding to Examples 4-5, the types of conductive agents were changed, and carbon nanotubes (CNT) and acetylene black (AB) were used to prepare electrodes, respectively. Batteries were assembled and tested to obtain charge and discharge curves and cycle performance graphs. In Example 5, the battery using carbon nanotubes (CNT) as a conductive agent had a discharge capacity of about 160 mAh g at a current density of 1C. -1 ( Figure 6a ), the capacity retention rate after 200 cycles is 99%, showing excellent cycle stability, but the battery polarization voltage is about 400mV ( Figure 6b ), which is larger than that of Example 1 when Ketjen black is used as the conductive agent (220 mV), indicating that the electrochemical reversibility of the battery is reduced. In Example 6, acetylene black (AB) is used as the conductive agent to assemble the battery. Figure 7a The battery can stably cycle 400 times and has an excellent cycle life, but the battery capacity is extremely low and the stability is poor, with a capacity of 75mAh g -1 There are multiple small fluctuations around the coulomb efficiency, which fluctuates between 97% and 99%, which may be related to the lower specific surface area and purity of acetylene black. Example 5-6 combined with Example 1 shows that the use of carbon materials with different high specific surface areas as conductive agents can cause sulfur self-diffusion at room temperature, and the positive electrode active material loading of >4 mg cm-3 can be successfully prepared by dry powder rolling. -2 The electrode can be used in medium-temperature molten salt aluminum-sulfur batteries.

[0129] Example 7: A mixture of sulfur (S) and selenium (Se) was used as the active material of the electrode, and a dry powder roller was used to prepare a 7 mg cm -2 High-capacity electrode. Figure 8a The battery exhibited a high first-cycle discharge capacity of 527 mAh g at a current density of 1C. -1 Although the battery only ran for 27 cycles, it is undeniable that the discharge capacity of this high-load battery has been significantly improved, and it has certain prospects. Compared with comparative example 2, a heat treatment step is added to the electrode preparation process to make the active material undergo thermal diffusion. The mixture of sulfur and selenium and the conductive agent Ketjen black are kept at 200°C under vacuum for 12 hours. The discharge capacity of the assembled battery at a current density of 1C is about 250 mAh g -1 ( Fig.10a ), the battery was cycled for only 11 cycles, and the battery discharge capacity and cycle number were much smaller than those in Example 7, indicating that the heat treatment step in the electrode preparation process had no beneficial effect on the battery performance, proving the non-essence of the hot-melt sulfur-selenium mixture, and indicating the rationality and excellence of the electrode preparation method of the present invention.

[0130] Fig.11 This is a self-made experimental diagram. The purpose of the experiment is to verify that sulfur can self-diffusion into Ketjen Black (KB) at room temperature, and further verify the non-necessity of the molten sulfur thermal diffusion step. Fig.11 (a), sulfur powder, diaphragm and Ketjen black powder were placed in a transparent glass bottle from top to bottom, and the glass bottle was filled with ethylene glycol dimethyl ether (DME), kept at room temperature, and the glass bottle was left standing in a glove box to observe the change of sulfur powder over time, where the sulfur powder was 30wt% of the Ketjen black mass, and the diaphragm was the diaphragm GF / D used for battery assembly. The experiment showed that as the number of days of standing increased, the sulfur powder gradually decreased visibly until the sulfur powder completely "disappeared" after the fifth day of standing, or the sulfur powder was completely diffused into the Ketjen black with high specific surface area and high porosity, achieving the effect of self-diffusion. Fig.11 (b) is the blank control group, without Ketchen black powder. Fig.11 (a) Under the same conditions, the sulfur content remained basically unchanged after five days, indicating that the "disappearance" of sulfur had nothing to do with the diaphragm and the solvent DME, but was only related to Ketjen black. This experimental result shows that sulfur can self-diffusion into Ketjen black with a high specific surface area at room temperature, further proving the rationality of the non-molten sulfur thermal diffusion step of the present invention.

[0131]

[0132]

[0133] The references are:

[0134] 1.Pang,Q.,et al.,Fast-charging aluminium-chalcogen batteriesresistant to dendritic shorting.Nature,2022.

[0135] 608(7924):p.704-711.

[0136] 2.Chu,W.Q.,et al.,A low-cost deep eutectic solvent electrolyte forrechargeable aluminum-sulfur battery.EnergyStorage Materials,2019.22:p.418-423.

[0137] 3.Li,H.,et al.,Reversible electrochemical oxidation of sulfur inionic liquid for high-voltage Al-S batteries.

[0138] Nature Communications,2021.12(1).

[0139] 4.Bian,Y.H.,et al.,Understanding the Oxidation and ReductionReactions of Sulfur in Rechargeable Aluminum-

[0140] Sulfur Batteries with Deep Eutectic Solvent and Ionic LiquidElectrolytes.Chemsuschem,2022.15(1).

[0141] 5.Ai,Y.F.,et al.,Bifunctional TiN@N-doped-graphene catalyst basedhigh sulfur content cathode for reversibleAluminum-Sulfur batteries.EnergyStorage Materials,2022.48:p.297-305.

[0142] 6.Zheng,X.,et al.,Design of a composite cathode and a graphene coatedseparator for a stable room-temperaturealuminum-sulfur battery.SustainableEnergy&Fuels,2020.4(4):p.1630-1641.

[0143] 7.Guo,Y.,et al.,Rechargeable Aluminium-Sulfur Battery with ImprovedElectrochemical Performance by Cobalt-Containing Electrocatalyst.AngewandteChemie-International Edition,2020.59(51):p.22963-22967.

[0144] 8.Huang,Z.,et al.,Electrocatalysis for Continuous Multi-StepReactions in Quasi-Solid-State ElectrolytesTowards High-Energy and Long-LifeAluminum-Sulfur Batteries.Angewandte Chemie-International Edition,2022.61(24).

[0146] 9.Hu,Z.Q.,et al.,Isolated Co single atoms in nitrogen-doped graphenefor aluminum-sulfur batteries withenhanced kinetic response.Journal of EnergyChemistry,2022.67:p.354-360.

[0147] 10.Ju, SL, et al., Identifying single-atom catalysts for boosted Al-Sconversion reactions. Energy Storage Materials, 2022.52: p.524-533.

[0149] 11.Guo,Y.,et al.,Carbonized-MOF as a Sulfur Host for Aluminum-SulfurBatteries with Enhanced Capacity andCycling Life.Advanced FunctionalMaterials,2019.29(7).

[0150] 12. Zhang, D., et al., Highly reversible aluminum-sulfur batteriesobtained through effective sulfur confinement with hierarchical porouscarbon. Journal of Materials Chemistry A, 2021.9(14):p.8966-8974.

[0151] In summary, the high-load positive electrode prepared in the present invention is applied in medium-temperature molten salt aluminum-sulfur batteries. The preparation process does not require the step of molten sulfur thermal diffusion, and the operation is simple. A more suitable active material loading is obtained by dry powder rolling and studying the conductive agent, the proportion of active materials and the electrode thickness. The assembled batteries can operate stably and show good electrochemical properties, indicating that the preparation method of the high-load electrode free of molten sulfur thermal diffusion of the present invention has a good prospect in battery application.

[0152] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a high-load positive electrode for a molten salt aluminum-sulfur battery, characterized in that: The following steps are involved: Step 1: Grind and evenly mix the active material and the conductive agent to obtain a mixture; the active material is sulfur or a sulfur-selenium mixture; Step 2: Add the binder to the mixture and press until the mixture gathers into a mass; Step 3: rolling the mass, gradually reducing the distance between the rollers, and rolling the mass multiple times until the mass is rolled to a desired thickness to obtain a sheet; Step 4: Dry and cut the sheet into pieces to obtain electrodes.

2. The method for preparing a high-load positive electrode for a molten salt aluminum-sulfur battery according to claim 1, characterized in that: In the step 1, the mass ratio of the active material to the conductive agent is (3-8):

2.

3. The method for preparing a high-load positive electrode for a molten salt aluminum-sulfur battery according to claim 1, characterized in that: In the step 1, the conductive agent is Ketjen black, carbon nanotubes or acetylene black.

4. The method for preparing a high-load positive electrode for a molten salt aluminum-sulfur battery according to claim 1, characterized in that: In the step 1, the active material and the conductive agent are ground using an agate grinder.

5. The method for preparing a high-load positive electrode for a molten salt aluminum-sulfur battery according to claim 1, characterized in that: In the step 2, the binder is polytetrafluoroethylene.

6. The method for preparing a high-load positive electrode for a molten salt aluminum-sulfur battery according to claim 1, characterized in that: In step 3, the thickness is 60 μm-160 μm.

7. The method for preparing a high-load positive electrode for a molten salt aluminum-sulfur battery according to claim 1, characterized in that: In step 3, the dough is rolled using an electric roller machine.

8. A method for preparing a molten salt aluminum-sulfur battery, characterized in that: The following steps are involved: S1. Prepare an electrode using the method according to claim 1; S2. Use the electrode prepared in S1 as the positive electrode of the battery, the aluminum sheet as the negative electrode, and an inorganic molten salt as the electrolyte to assemble the battery.

9. The method for preparing a molten salt aluminum-sulfur battery according to claim 8, characterized in that: In the step S2, the inorganic molten salt is a quaternary inorganic molten salt or a quaternary inorganic molten salt saturated with aluminum sulfide.

10. The method for preparing a molten salt aluminum-sulfur battery according to claim 9, characterized in that: The quaternary molten salt is a mixture of aluminum chloride (AlCl3), sodium chloride (NaCl), lithium chloride (LiCl) and potassium chloride (KCl).

Citation Information

Patent Citations

  • Anti-rolling lithium-sulfur battery positive plate and preparation method thereof

    CN112687841A

  • Positive pole piece for lithium-sulfur battery and preparation method of positive pole piece

    CN114512632A

  • Secondary battery

    JP2004342575A

  • Lithium-sulfur battery

    US20180175375A1